A Multi-Informant Multi-Method Investigation of Family Functioning and Parent–Child Coping During Children's Acute Pain. (13th June 2016) - Birnie, Kathryn A.; Chambers, Christine T.; Chorney, Jill; Fernandez, Conrad V.; McGrath, Patrick J.
Abstract : Objective To explore relations between family functioning and child acute pain, including pain ratings, coping, and parent–child behaviors. Methods Community sample of 171 dyads including one child aged 8–12 years (52% girls) and one parent (79% mothers). Family functioning was assessed via child and parent self-report, and observation during a conflict discussion task. Children and parents rated pain catastrophizing at baseline, and child pain and distress following a cold pressor task (CPT). Parent–child interactions during the CPT were coded for observed behaviors during child pain. Results Self-report of poorer family functioning predicted greater child and parent pain catastrophizing, and parent distress. Less observed family negativity/conflict and cohesiveness, and greater family focus of problems and parent emotional support predicted more child symptom complaints. Family functioning was not associated with child pain or distress. Conclusions Family functioning influenced parent and child coping and child behavioral responses, but not the experience, of acute pain.